2021
DOI: 10.15585/mmwr.mm7048a4
|View full text |Cite
|
Sign up to set email alerts
|

Notes from the Field: COVID-19 Vaccination Coverage Among Persons Experiencing Homelessness — Six U.S. Jurisdictions, December 2020–August 2021

Abstract: COVID-19 outbreaks have been reported in homeless shelters across the United States (1). Many persons experiencing homelessness are older adults or persons with underlying medical conditions, placing them at increased risk for severe COVID-19-associated illness. The proportion of persons experiencing homelessness who are fully vaccinated against COVID-19 in the United States is currently unknown. Many persons experiencing homelessness express a willingness to receive the COVID-19 vaccine (2,3).Through conversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…Finally, the few studies to date that have investigated vaccine coverage among PEH report low coverage compared with the general population. US-based estimates place coverage among PEH 11.0%–37.2% lower than the general US population 31 32. Another recent Canadian study suggests vaccination rates among Ontario PEH who use healthcare are 25% lower than that of adult Ontarians 33…”
Section: Background and Rationalementioning
confidence: 99%
“…Finally, the few studies to date that have investigated vaccine coverage among PEH report low coverage compared with the general population. US-based estimates place coverage among PEH 11.0%–37.2% lower than the general US population 31 32. Another recent Canadian study suggests vaccination rates among Ontario PEH who use healthcare are 25% lower than that of adult Ontarians 33…”
Section: Background and Rationalementioning
confidence: 99%
“…This study also sheds light on opportunities to improve access to scientific information about COVID-19 vaccines. Although there seems to be acceptance of COVID-19 vaccines and the concerns expressed about vaccines are not remarkably different from the general population, COVID-19 vaccine coverage is still significantly lower among PEH than the general population 9,10. Improving vaccine confidence and reducing barriers to vaccination are especially important for people who may be receiving services in congregate settings, even if they spend most of their time outdoors.…”
Section: Discussionmentioning
confidence: 99%
“…7 , 8 Overall vaccination levels in the homeless community lag an estimated 15–25% behind levels observed in the population generally. 9 One study in Los Angeles found that 58% of young adults experiencing homelessness reported that they had not been offered a vaccine, suggesting a further problem of inadequate vaccine access and outreach. 10 Active vaccine outreach is especially important among people experiencing homelessness because of the long history of marginalization, mistreatment, stigma, and substandard care this population has experienced from healthcare providers.…”
Section: Introductionmentioning
confidence: 99%